CYGNO: Triple-GEM Optical Readout for Directional Dark Matter Search. (April 2020) - Abritta Costa, I.; Baracchini, E.; Bedogni, R.; Bellini, F.; Benussi, L.; Bianco, S.; Caponero, M.; Cavoto, G.; Di Marco, E.; D'Imperio, G.; Maccarrone, G.; Marafini, M.; et al.
Abstract: CYGNO is a project realising a cubic meter demonstrator to study the scalability of the performance of the optical approach for the readout of large-volume, GEM-equipped TPC. This is part of the CYGNUS proto-collaboration which aims at constructing a network of underground observatories for directional Dark Matter search. The combined use of high-granularity sCMOS and fast sensors for reading out the light produced in GEM channels during the multiplication processes was shown to allow on one hand to reconstruct 3D direction of the tracks, offering accurate energy measurements and sensitivity to the source directionality and, on the other hand, a high particle identification capability very useful to distinguish nuclear recoils. Results of the performed R&D and future steps toward a 30-100 cubic meter experiment will be presented.